2011
DOI: 10.1007/s00726-011-0907-1
|View full text |Cite
|
Sign up to set email alerts
|

Low amino acids affect expression of 11β-HSD2 in BeWo cells through leptin-activated JAK-STAT and MAPK pathways

Abstract: Maternal protein restriction diminishes placental 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) activity and causes fetal growth restriction in mammals. However, it is unknown whether such effect was caused directly by nutrient deficiency, or indirectly through the mediation of maternal hormones. In the present study, a human placental cell line (BeWo) was cultured in F12K as control and F12 as low amino acids (LAA) media for 48 h to investigate the effects of amino acids deficiency on 11β-HSD2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…Downregulation of miR-498 was also found in the nasal mucosa of allergic rhinitis patients [64]. In addition, miR-498 was has recently been reported to play a possible role in translational repression of 11β-hydroxysteroid dehydrogenase type 2 mRNA in BeWo cells (human placental cell line) subjected to amino acid deficiency [65]. However, in our study, miR-498 and miR-320d played an important role in regulating KSHV replication.…”
Section: Discussioncontrasting
confidence: 43%
“…Downregulation of miR-498 was also found in the nasal mucosa of allergic rhinitis patients [64]. In addition, miR-498 was has recently been reported to play a possible role in translational repression of 11β-hydroxysteroid dehydrogenase type 2 mRNA in BeWo cells (human placental cell line) subjected to amino acid deficiency [65]. However, in our study, miR-498 and miR-320d played an important role in regulating KSHV replication.…”
Section: Discussioncontrasting
confidence: 43%
“…34 Shang et al 34 starved a human placental cell line (BeWo) from amino acids and observed a decline in the 11β-HSD2 activity, which was unexplained by a change in HSD11B2 mRNA abundance. The authors checked the expression of 5 different miRNAs for potential underlying mechanisms and found a significant increase in miR-498 level after cellular starvation.…”
Section: Discussionmentioning
confidence: 99%
“…How the miRNAs were selected for testing was not reported. 34 By using 3 miRNA target prediction programs (described above), we identified a weak prediction for miR-498 binding to the 3′-UTR of HSD11B2 only by miRanda. In our analysis of CCDs, miR-498 was not identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13]. Numerous reports have indicated that 11β-HSD2 can be regulated by MAPKs signalling [32], [33]. Furthermore, MAPKs have been proven to modify GC sensitivity, namely that the activation of extracellular signal-regulated protein kinase (ERK) and p38 MAPK reduce and enhance GC sensitivity, respectively [16].…”
Section: Discussionmentioning
confidence: 99%